Endothelial response to glucose: dysfunction, metabolism, and transport - Clyne, Alisa Morss (Biochemical Society transactions, 2021)
The endothelial cell response to glucose plays an important role in both health and disease. Endothelial glucose-induced dysfunction was first studied in diabetic animal models and in cells cultured in hyperglycemia. Four classical dysfunction pathways were identified, which were later shown to result from the common mechanism of mitochondrial superoxide overproduction. More recently, non-coding RNA, extracellular vesicles, and sodium-glucose cotransporter-2 inhibitors were shown to affect glucose-induced endothelial dysfunction. Endothelial cells also metabolize glucose for their own energetic needs. Research over the past decade highlighted how manipulation of endothelial glycolysis can be used to control angiogenesis and microvascular permeability in diseases such as cancer. Finally, endothelial cells transport glucose to the cells of the blood vessel wall and to the parenchymal tissue. Increasing evidence from the blood-brain barrier and peripheral vasculature suggests that endothelial cells regulate glucose transport through glucose transporters that move glucose from the apical to the basolateral side of the cell. Future studies of endothelial glucose response should begin to integrate dysfunction, metabolism and transport into experimental and computational approaches that also consider endothelial heterogeneity, metabolic diversity, and parenchymal tissue interactions.